TINGKAT PENGETAHUAN SISWA DENGAN PERILAKU KEBIASAAN MENGKONSUMSI JAJANAN BERBAHAYA DI DESA SUKAHARJA RW 04 SINDANG JAYA KABUPATEN TANGERANG - Nurul Hasanah (Nusantara Hasana Berdikari, 2021)
Snacks are food and drink that are prepared and sold by street vendors on the streets or other public places which are usually consumed directly whitout further processing. Dangerous substances contained in school snacks can cause acute reactions in the body, in the form of coughing, diarrhea, difficulty defecating or poisoning. Research aims to determine the relationship of the level of knowledge og students in grades 4 and 5 to the habit of consuming dangerous snacks in Sukaharja Village Sindang Jaya Sub-District Tangerang District. The research method uses a quantitative research design with a cross sectional approach. Total sampling technique with sample count of 102 respondents. Chi square test result show the value of sig p-value 0.035 < 0.05, meaning there is relationship of the level of knowledge of students in grades 4 and 5 to the habit of consuming dangerous snacks in Sukaharja Village Sindang Jaya Sub-District Tangerang District. The highest results obtained are the level of knowledge that is less as much 38 respondents (37,3%), positive habits of 67 respondents (65,7%), for that is expected to encourage parents to better provide information related what snacks are good and not good for consumption by children, so that they can choose the type of food that is safe and healthy for the body.